2020
DOI: 10.1002/slct.202002183
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Thermal Properties and Reliability Testing of Binary Eutectic Mixture of Polyethylene Glycol 2000 and 10000 as Phase Change Materials

Abstract: This experimental investigation presents the two major aspects of thermal energy storage materials. One is development of eutectic mixtures of polyethylene glycols (PEGs) and another is thermal reliability of them. The commercial grade PEGs with molecular mass 2000 and 10000 were mixed in different mass fractions via facile incorporation method for preparing the eutectic mixtures. The thermal energy storage capacity was measured by using differential scanning calorimeter (DSC) and Fourier transform and infrare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Since thermal cycling does not change the chemical structure of the sample, it is more likely to be attributed to impurities in the sample. [ 35,36 ] It can be concluded that EPCMTS composite has fairly good thermal reliability after 150 thermal cycles.…”
Section: Resultsmentioning
confidence: 99%
“…Since thermal cycling does not change the chemical structure of the sample, it is more likely to be attributed to impurities in the sample. [ 35,36 ] It can be concluded that EPCMTS composite has fairly good thermal reliability after 150 thermal cycles.…”
Section: Resultsmentioning
confidence: 99%
“…The organic phase change materials are more preferred over inorganic as they show no/little supercooling effect, non‐corrosive and have good latent heat capacity [4–5] . Eutectics are basically a combination of more than one material and it can be either organic‐inorganic, organic‐organic, or inorganic‐inorganic materials [6–7] . Despite of several advantages, O‐PCMs also have a major shortcoming of suppressed thermal conductivity, which directly hampers their heat transmission rate.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5] Eutectics are basically a combination of more than one material and it can be either organic-inorganic, organicorganic, or inorganic-inorganic materials. [6][7] Despite of several advantages, O-PCMs also have a major shortcoming of suppressed thermal conductivity, which directly hampers their heat transmission rate. This eventually impacts charging and discharging rate of O-PCMs.…”
Section: Introductionmentioning
confidence: 99%